2023
DOI: 10.1021/acsestengg.2c00379
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Novel Cyclodextrin Polymer Granules to Remove Perfluoroalkyl Acids (PFAAs) from Water

Abstract: Cyclodextrin polymers (CDPs) are promising adsorbents for the removal of per- and polyfluoroalkyl substances (PFASs) from water. For CDPs to be implemented in packed-bed filtration (PBF) systems, CDP powders must be processed to produce CDP granules of a defined size. In this study, we introduce CDP granules with average particle diameters (d p) of 84–718 μm produced from a CDP powder by means of high-shear spray granulation. We evaluated the performance of the CDP granules in batch studies to evaluate the ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
(160 reference statements)
1
7
0
Order By: Relevance
“…The high affinity of Cationic StyDex toward the selected PFAS in wastewater is consistent with equilibrium adsorption and kinetics results, in which Cationic StyDex demonstrated nearly complete PFAS removal with the fastest adsorption kinetics out of the three adsorbents. The affinity trend of Cationic StyDex toward the selected PFAS, PFHxS (3.58 ± 0.27 L g –1 ) > PFOA (2.72 ± 0.33 L g –1 ) > PFHxA (1.82 ± 0.24 L g –1 ), is also consistent with our previous report that evaluated different sized β-CD polymer granules (prepared based on the previous generation of cross-linking chemistry) for PFAS removal in nanopure water …”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The high affinity of Cationic StyDex toward the selected PFAS in wastewater is consistent with equilibrium adsorption and kinetics results, in which Cationic StyDex demonstrated nearly complete PFAS removal with the fastest adsorption kinetics out of the three adsorbents. The affinity trend of Cationic StyDex toward the selected PFAS, PFHxS (3.58 ± 0.27 L g –1 ) > PFOA (2.72 ± 0.33 L g –1 ) > PFHxA (1.82 ± 0.24 L g –1 ), is also consistent with our previous report that evaluated different sized β-CD polymer granules (prepared based on the previous generation of cross-linking chemistry) for PFAS removal in nanopure water …”
Section: Resultssupporting
confidence: 91%
“…The authors demonstrated that RSSCT can be applied for the removal of the tested PFAS onto the IX resins . We previously applied RSSCT under both CD and PD designs to evaluate different sized β-CD polymer (CDP) granules based on the previous generation of cross-linking chemistry and found that neither the assumption of CD nor PD was unequivocally appropriate for CDP granules . Therefore, an improved understanding of mass transfer limitations of these novel adsorbents as a function of particle size will be desirable, as they are scaled to pilot-sized systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative paucity of highly performant linear probe molecules identified by our ML-enabled workflow militates for an expansion of the molecular search space to molecular libraries containing a richer chemical diversity of candidate molecules including branched and cyclic hydrocarbons, as well as more exotic molecules such as cyclodextrin-based probes that have garnered some attention and success in PFAS sequestration. , Further enlargements of the design space can make the computational screening platform established in this work even more valuable in performing an efficient filtration of the enlarged design space to identify the most promising molecular probes to be explored experimentally and also in excavating a molecular-level understanding of probe performance that can be coupled with experimental intuition to help inform rational molecular design. The performance of our active learning pipeline in achieving convergence after considering only 6% of the molecular space provides support for its capacity to efficiently navigate and traverse large search spaces and quickly focus on the most promising candidates.…”
Section: Discussionmentioning
confidence: 99%